State of an art review of peat: general perspective - Kim Huat, Bujang; Kazemian, Sina; Prasad, Arun; Barghchi, Maassoumeh (Academic Journals, 2011)
Peat can be defined as the accumulation of 100% pure organic material which contains at least 65% organic matter or less than 35% mineral content. The distribution of peat deposits is extensive. It constituents 5 to 8% of the earth land surface and nearly 60% of the wetlands of the world are peat. The composition of peat differs from location to location. This is due to the reasons such as the origin fibre, climate and humidity. Physical properties of peat are greatly dependent to a large degree on porosity and pore-size distribution. These in turn are related to particle-size distribution. Both the particle size and structure and the resulting porosity of peat are controlled primarily by the degree of decomposition. With increasing decomposition, the size of organic particles decreases, resulting in smaller pores and more dry material per unit volume. Generally, the texture of peat is considered coarse when compared with clay. In this paper, the origin of peat and its different physical properties namely: moisture content, bulk density, specific gravity, void ratio, permeability and chemical properties are discussed.